Download presentation
Presentation is loading. Please wait.
1
Solving Systems of Equations
The Elimination Method
2
Objectives Learn the procedure of the Elimination Method using addition Learn the procedure of the Elimination Method using multiplication Solving systems of equations using the Elimination Method
3
Solving a system of equations by substitution
Pick the easier equation. The goal is to get y= ; x= ; a= ; etc. Step 1: Solve an equation for one variable. Step 2: Substitute Put the equation solved in Step 1 into the other equation. Substitute the value of the variable into the equation. Step 3: Plug back in to find the other variable. Step 4: Check your solution. Substitute your ordered pair into BOTH equations.
4
1) Solve the system using substitution
x + y = 5 y = 3 + x Step 1: Solve an equation for one variable. The second equation is already solved for y! Step 2: Substitute x + y = 5 x + (3 + x) = 5 2x + 3 = 5 2x = 2 x = 1
5
1) Solve the system using substitution
x + y = 5 y = 3 + x x + y = 5 (1) + y = 5 y = 4 Step 3: Plug back in to find the other variable. (1, 4) (1) + (4) = 5 (4) = 3 + (1) Step 4: Check your solution. The solution is (1, 4). What do you think the answer would be if you graphed the two equations?
6
Elimination using Addition
Consider the system x - 2y = 5 Lets add both equations to each other 2x + 2y = 7 REMEMBER: We are trying to find the Point of Intersection. (x, y)
7
Elimination using Addition
Consider the system x - 2y = 5 Lets add both equations to each other + 2x + 2y = 7 NOTE: We use the Elimination Method, if we can immediately cancel out two like terms.
8
Elimination using Addition
Consider the system x - 2y = 5 Lets add both equations to each other + 2x + 2y = 7 3x = 12 x = 4 ANS: (4, y) NOTE: We use the Elimination Method, if we can immediately cancel out two like terms.
9
Elimination using Addition
Consider the system x - 2y = 5 Lets substitute x = 4 into this equation. 2x + 2y = 7 4 - 2y = 5 Solve for y - 2y = 1 y = 1 2 ANS: (4, y) NOTE: We use the Elimination Method, if we can immediately cancel out two like terms.
10
Elimination using Addition
Consider the system x - 2y = 5 Lets substitute x = 4 into this equation. 2x + 2y = 7 4 - 2y = 5 Solve for y - 2y = 1 1 2 y = 1 2 ANS: (4, ) NOTE: We use the Elimination Method, if we can immediately cancel out two like terms.
11
Elimination using Addition
Consider the system 3x + y = 14 4x - y = 7 NOTE: We use the Elimination Method, if we can immediately cancel out two like terms.
12
Elimination using Addition
Consider the system 3x + y = 14 + 4x - y = 7 7x = 21 x = 3 ANS: (3, y)
13
Elimination using Addition
Consider the system 3x + y = 14 Substitute x = 3 into this equation 4x - y = 7 3(3) + y = 14 9 + y = 14 y = 5 ANS: (3, ) 5 NOTE: We use the Elimination Method, if we can immediately cancel out two like terms.
14
Examples… 1. 2. ANS: (4, -3) ANS: (-1, 2)
15
Elimination using Multiplication
Consider the system 6x + 11y = -5 6x + 9y = -3
16
Elimination using Multiplication
Consider the system 6x + 11y = -5 + 6x + 9y = -3 12x + 20y = -8 When we add equations together, nothing cancels out
17
Elimination using Multiplication
Consider the system 6x + 11y = -5 6x + 9y = -3
18
Elimination using Multiplication
Consider the system -1 ( ) 6x + 11y = -5 6x + 9y = -3
19
Elimination using Multiplication
Consider the system - 6x - 11y = 5 + 6x + 9y = -3 -2y = 2 y = -1 ANS: (x, ) -1
20
Elimination using Multiplication
Consider the system 6x + 11y = -5 6x + 9y = -3 Lets substitute y = -1 into this equation y = -1 6x + 9(-1) = -3 6x + -9 = -3 +9 6x = 6 x = 1 ANS: (x, ) -1
21
Elimination using Multiplication
Consider the system 6x + 11y = -5 6x + 9y = -3 Lets substitute y = -1 into this equation y = -1 6x + 9(-1) = -3 6x + -9 = -3 +9 6x = 6 x = 1 ANS: ( , ) 1 -1
22
Elimination using Multiplication
Consider the system x + 2y = 6 Multiply by -3 to eliminate the x term 3x + 3y = -6
23
Elimination using Multiplication
Consider the system -3 ( ) x + 2y = 6 3x + 3y = -6
24
Elimination using Multiplication
Consider the system -3x + -6y = -18 + 3x + 3y = -6 -3y = -24 y = 8 ANS: (x, 8)
25
Elimination using Multiplication
Consider the system x + 2y = 6 Substitute y =14 into equation 3x + 3y = -6 y =8 x + 2(8) = 6 x + 16 = 6 x = -10 ANS: (x, 8)
26
Elimination using Multiplication
Consider the system x + 2y = 6 Substitute y =14 into equation 3x + 3y = -6 y =8 x + 2(8) = 6 x + 16 = 6 x = -10 ANS: ( , 8) -10
27
Examples 1. 2. x + 2y = 5 x + 2y = 4 2x + 6y = 12 x - 4y = 16
ANS: (3, 1) ANS: (8, -2)
28
More complex Problems Consider the system 3x + 4y = -25 Multiply by 2
29
More complex Problems Consider the system 2( ) 3x + 4y = -25 -3( )
2( ) 3x + 4y = -25 -3( ) 2x - 3y = 6
30
More complex Problems + Consider the system 6x + 8y = -50
ANS: (x, -4)
31
More complex Problems Consider the system 3x + 4y = -25 2x - 3y = 6
Substitute y = -4 2x - 3(-4) = 6 2x = 6 2x + 12 = 6 2x = -6 x = -3 ANS: (x, -4)
32
More complex Problems Consider the system 3x + 4y = -25 2x - 3y = 6
Substitute y = -4 2x - 3(-4) = 6 2x = 6 2x + 12 = 6 2x = -6 x = -3 ANS: ( , -4) -3
33
Examples… 2. 1. 2x + 3y = 1 4x + y = 9 5x + 7y = 3 3x + 2y = 8
ANS: (2, 1) ANS: (2, -1)
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.